Evaluation of Instructor-Generated Vs. Student-Generated Content in Online Humanities Courses in South Africa - Fassie, Brenda (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the evaluation of instructor-generated vs. student-generated content in online humanities courses in South Africa. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Studies comparing instructor-generated and student-generated content in online humanities courses in South Africa indicate that instructor-generated content offers structured and consistent learning materials aligned with course objectives. Conversely, student-generated content enhances engagement, critical thinking, and collaborative skills among learners. Effective use of both approaches, tailored to course topics and student demographics, could optimize online humanities education outcomes in South Africa by balancing instructional guidance with student autonomy and creativity. Unique Contribution to Theory, Practice and Policy: Constructivist learning theory, community of inquiry framework & self-determination theory may be used to anchor future studies on the evaluation of instructor-generated vs. student-generated content in online humanities courses in South Africa. Equip educators with pedagogical strategies that leverage both instructor expertise and student autonomy. Inform curriculum design policies that advocate for the integration of diverse content generation methods across humanities disciplines.